0304 The NIEHS GuLF STUDY: Estimate of workers' exposures through the inhalation route on seven response vessels near the well-site during the Deepwater Horizon oil spill. (23rd June 2014) - Ramachandran, Gurumurthy; Huynh, Tran; Banerjee, Sudipto; Groth, Caroline; Stenzel, Mark; Blair, Aaron; Engel, Lawrence; Sandler, Dale; Kwok, Richard; Stewart, Patricia
Abstract : Objectives: After the Deepwater Horizon, response vessels were brought near the wellhead area to stop the leak, collect oil and drill the relief wells. The objective of this paper is to characterise inhalation exposure on these vessels for various exposure groups (EGs) to total hydrocarbons (THCs). Method: Approximately 100 EGs based on job title group, tasks and time period during the response effort were standardised across these vessels. Descriptive statistics were calculated from the measurements for each EG on each vessel. Since many of the data were censored (i.e., below the limit of detection), a Bayesian method was used to obtain estimates for the arithmetic mean (AM), geometric mean, and geometric standard deviation. Results: During the first time period (April 20–May 14), the range of the AMs on the vessels was 1.9–24.2 ppm THC. Exposures were lower during the second period (May 15–July 15) when dispersant was used to reduce air concentrations (0.1–14.6 ppm). After top-capping the well, a substantial reduction was observed on all seven ships (0.1–1.9 ppm). After bottom capping (>August 10), exposures generally increased on the ships (0.1–3.8 ppm), most likely due to decontamination activities. The vessel capping the well and the vessel burning waste oil and gas had significant differences from the vessels drilling the relief wells. Conclusions: Differences were found by vessel and time period that likely reflected oil weathering and differences in job and vessel activities.